The effect(s) of mask alignment to P-N junction / Ahd Syarifuddin Mohd Helmi - Mohd Helmi, Ahd Syarifuddin (2010)
[1]This study simplify the mask alignment process in fabrication of a simple p-n junction. [2]Optimize the dimension of the device where the pattern is easy to be transfer on the wafer in fabricating a simple p-n junction. [3]To design a suitable mask that is easy to transfer the pattern on the wafer to fabricate p-n junction.